2015
DOI: 10.1080/11250003.2015.1106012
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the phylogeography ofPinctada imbricata radiata(Leach, 1814) (Bivalvia: Pteriidae) from the Eastern Mediterranean Sea by means of the mitochondrialCOImarker

Abstract: Pinctada imbricata radiata (Leach, 1814) was the first Lessepsian bivalve reported in the Mediterranean Sea where it is progressively expanding westward. Its native range includes the Indian Ocean and western Atlantic. The present study provides the first insight into the species' phylogeographic structure, by analysing sequences of a 385-bp region of the mitochondrial gene coding for the subunit I of the cytochrome c oxydase (COI). Sixty-four individuals collected at seven Mediterranean localities were sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…The disagreement of the present conclusions with previous molecular studies ( Barbieri et al, 2015) according to us is attributable to the low number of specimens tested in these latter.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The disagreement of the present conclusions with previous molecular studies ( Barbieri et al, 2015) according to us is attributable to the low number of specimens tested in these latter.…”
Section: Discussioncontrasting
confidence: 99%
“…But the genetic diversity of populations of this species in the basin seems to exhibit low values, as reported by Barbieri et al (2015).…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although these sequences were not analysed in comparison to our haplotypes owing to their much shorter available sequences, our results are in total agreement with these inferences concerning haplotype and nucleotide diversity. BLAST results of the P. radiata COI sequence obtained from the three locations of Greece were 99.22-100% similar to the ten haplotypes reported by Barbieri et al (2016) from the Eastern Mediterranean, while the haplotype H2 from these authors which was the prevalent haplotype among seven geographic areas of the Eastern Mediterranean was 100% similar to our haplotype. The low level of population subdivision seems to be mainly assigned to the long pelagic larval stage of this bivalve.…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 87%
“…In our study this species was found panmictic at three sampling geographic areas, presenting zero differences in the both sequences of COI and 18S rRNA. Other authors also detected low haplotype and nucleotide diversity in P. radiata specimens among different sampling areas (Meyer et al, 2013;Barbieri et al, 2016) while at Adriatic Sea (Sobra Bay) and at United Arab Emirates high haplotype along with low nucleotide diversity was found by Gavrilović et al (2017) and Cunha et al (2011) respectively. Although these sequences were not analysed in comparison to our haplotypes owing to their much shorter available sequences, our results are in total agreement with these inferences concerning haplotype and nucleotide diversity.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 87%